Development of Learning Media in The Subject of Network Infrastructure Administration - Putra, Rezi Septiardi; Fadhilah; Ta’ali; Wakhinuddin S (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
This research aims to develop learning media for class The research method used is the R&D method using the four-D development model. The four-D development model consists of Define, Design, Development, and Disseminate. The results obtained from this development research are learning media based on Adobe Flash Professional CS6. Based on the research results, it can be concluded that the media developed is declared valid in the media aspect at 85.42%, the material aspect with results at 80.83%. The media developed is practical with a practical value from teacher responses with results of 90.14% and student responses of 89.60%, and the resulting learning media has been effectively used with posttest results seen from students' classical completeness of 88% and a gain score of 0 .38 in the medium category. The conclusion is that the Adobe Flash Professional CS6-based learning media developed can be used and is feasible in the learning process to improve student learning outcomes. Learning Media, Adobe Flash Professional CS6, Network Infrastructure Administration